Estudio de prefactibilidad para la instalación de una planta productora de bolsas biodegradables a partir de ácido poliláctico - Tello Ortiz de Zevallos, Andrea (2021)
The pollution is caused by the excessive use of plastics which, when discarded, accumulate both at sea and on land. Our country generates 6. 8 million tons solid wastes per year, of which 11% are plastics, among which are the bags that consume about 3 billion units per year. Due to this situation, the idea of implementing a biodegradable bag plant was born, from polylactic acid, a biopolymer that ensures that the absolute degradation of the product occurs in a shorter time than conventional bags and above all makes use of renewable resources such as corn. Also, the growing concern of people for the care of the environment and the use of environmentally friendly products. It is therefore considered a business opportunity to enhance the biodegradable options industry.